Characterization of enameled glass excavated from Laem Pho, southern Thailand - Dhanmanonda W. (2014)
Laem Pho in Surat Thani, southern province of Thailand is one of the most important historic site on the eastern shore of the Gulf of Thailand. In this work, the enameled glass fragments which looked-like Islamic glass mainly excavated from this site were analyzed using SEM-EDS, PIXE and μ-XRF, in order to understand the chemical composition by comparing the archaeological data and topology. The structure of the enameled decoration was also studied. The resulting data indicated that high-magnesia alkali-lime silicate glass was produced. The presence of transition metals such as copper, iron and manganese were affected on the glass colorations. Typological classifications, technological observations and comparative studies serve to clarify the development and cultural inter-relationships of various glass objects along the trade and exchange networks in ancient maritime. © Published under licence by IOP Publishing Ltd.